Metastasis Research Protocols
DOI: 10.1385/1-59259-137-x:055
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cell Motility: Gold Colloidal Phagokinetic Track Assay and Wound Healing Assay

Abstract: Cellular migration is an integral aspect in response to extracellular stimuli, which is fundamental to numerous biological processes such as embryogenesis, inflammation, wound healing, tissue regeneration, and tumor invasion and metastasis (1,2). Abundant studies centered on the identification and characterization of factors that regulate and direct cell movement have shown that host serum components and extracellular matrix breakdown products exert a chemotactic effect on various tumor cells (3) and that base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 2 publications
0
23
0
Order By: Relevance
“…Twenty-four-well plates were uncoated or coated with 10 Ag/mL collagen I (BD Biosciences) to facilitate rapid cell attachment (26). Cells were seeded at 1 Â 10 5 to 2 Â 10 5 per well and allowed to attach.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-four-well plates were uncoated or coated with 10 Ag/mL collagen I (BD Biosciences) to facilitate rapid cell attachment (26). Cells were seeded at 1 Â 10 5 to 2 Â 10 5 per well and allowed to attach.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, hexokinase, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and enolase have been implicated to play a role in transcriptional regulation (Niederacher and Entian, 1991;Herrero et al, 1995;Feo et al, 2000;Rodriguez et al, 2001;Zheng et al, 2003). Hexokinase and GAPDH may regulate apoptosis (Ishitani and Chuang, 1996;Shashidharan et al, 1999;Tajima et al, 1999;Dastoor and Dreyer, 2001;Gottlob et al, 2001;Pastorino et al, 2002;Rathmell et al, 2003;Majewski et al, 2004), and glucose-6-phosphate isomerase can affect cell motility (Liotta et al, 1986;Nabi et al, 1990;Watanabe et al, 1996;Niinaka et al, 1998;Sun et al, 1999). Furthermore, although glycolysis is the classical metabolic pathway that generates pyruvate, other metabolic reactions such as conversion of xylulose-5-phosphate to glyceraldehyde-3-phosphate through the pentose phosphate pathway by transketolase also produce the metabolic intermediate that channel to the second phase of the glycolytic pathway ( Figure 1, dashed arrows), yielding pyruvate and ATP.…”
Section: The Glycolytic Pathwaymentioning
confidence: 99%
“…Interestingly, recent studies have revealed that GPI can also function as an autocrine motility factor (AMF), which is secreted from the tumor cells to promote cell motility and proliferation (Niinaka et al, 1998;Sun et al, 1999). Autocrine motility factor and its receptor AMFR (gp78) were originally identified in melanoma and oncogenetransfected metastatic NIH3T3 cells, and the AMF/ AMFR interaction seems to stimulate tumor cell migration in vitro and enhance metastasis and angiogenesis in vivo (Liotta et al, 1986;Nabi et al, 1990;Watanabe et al, 1996;Funasaka et al, 2001Funasaka et al, , 2002.…”
Section: Glucose-6-phosphate Isomerasementioning
confidence: 99%
“…9). Molecular cloning and sequencing have identified PGI as an autocrine motility factor (AMF), which is originally identified as a major cell motility-stimulating factor associated with cancer progression and metastasis (8,10,11). PGI/AMF was independently identified as neuroleukin that promotes growth of embryonic spinal and sensory neurons (12), maturation factor mediating differentiation of human myeloid leukemia cells (13), sperm antigen-36 (14), and myofibril-bound serine proteinase inhibitor (15).…”
mentioning
confidence: 99%